Projeto experimental de publicidade e propaganda: Associação Lagoense protetora dos animais - Focinhos Carentes - Dalmina, Daniela da Silva (2018)
The implementation of this work was intended to elaborate and produce an experimental project for the Advertising and Propaganda course, carrying out research, planning and creation of a communication campaign in which the non-governmental organization Focinhos Carentes, located in Lagoa Vermelha / RS, which acts in the defense and protection of animals. The general objective of this work was to elaborate a communication plan for the 12-month period, with specific objectives, to understand the communication failures of the institution, to suggest effective communication strategies to reinforce the institution's position and image, to know the vision the creation of a Visual Identity Manual (MIV), assisting in the supply and maintenance of communication aligned in digital networks, intensifying relationships with the public, and instigating and fostering loyalty or volunteering. The construction methodology was developed from: briefing and brainstorming. It was possible to identify positive results, both planning and creation are effective for the organization, taking into account their real problems.